Pinhole surgical technique – A novel minimally invasive approach for treatment of multiple gingival recession defects: A case series - Manvi Chandra Agarwal; Geetika Kumar; R G Shiva Manjunath; S S Sai Karthikeyan; Shiva Shankar Gummaluri (Contemporary Clinical Dentistry, 2020)
Gingival recessions are one of the most prevalent periodontal diseases. Hypersensitivity and esthetics are the major concerns associated with recession defects. There are various treatment modalities for its management, but recently, minimally invasive techniques have gained much importance because of lower patient morbidity and comparable results when compared to conventional techniques. This case series represents a 6-month follow-up of a recently introduced pinhole surgical technique where the percentage of root coverage was found to be statistically significant.